Hubungan murajaah Al-Qur’an terhadap karakter disiplin dan sikap spiritual siswa di SD Tahfidzul Qur’an Darul Abror - Urrokhmah, Syifa; Toharudin, Moh.; Sunarsih, Diah (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Education is an effort made by every human being consciously to improve the quality and attitude within him. This study aims to determine the relationship between murajah Al-Qur'an and the character of discipline and spiritual attitudes of students at SD Tahfidzul Qur'an Darul Abror. The method used in this research is correlational quantitative. The sampling technique used is the saturated sampling technique, which makes the entire population the sample in the study. The data obtained came from observation sheets and questionnaires. Observation sheets were used to collect data on the murajaah of the Qur'an, and questionnaires were used to collect data on the character of discipline and spiritual attitudes. The results of this study show that the results of the partial test (t test) on the X variable (murajaah) against the Y1 variable (discipline character) show that the two variables have a significant relationship. The results of the F test show that there is a relationship between the variables X (murajaah) and Y1 (discipline character) and Y2 (spiritual attitude). Variable X (murajaah) has the strongest relationship to variables Y1 (discipline character) and Y2 (spiritual attitude) because it has the largest regression coefficient value of 4.492. The coefficient of determination, or R2 (R Squere), is 0.636. This means that the large percentage of the relationship between the murajaah of the Qur'an on the character of discipline and spiritual attitudes is 63%, and 47% is influenced by other variables outside the study.